Biology of Fopius arisanus (Hymenoptera: Braconidae) in Two Species of Fruit Flies. Issue 1 (25th August 2016) - Groth, M. Z.; Loeck, A. E.; Nörnberg, S. D.; Bernardi, D.; Nava, D. E.
Abstract: Fopius arisanus (Sonan, 1932) (Hymenoptera: Braconidae) is an egg–larval parasitoid used in control programs of Bactrocera dorsalis (Hendel) and Ceratitis capitata (Wiedemann). In Brazil, C. capitata and Anastrepha fraterculus (Wiedemann) are considered the main tephritid pests of exotic and indigenous fruits. The objective of this study was to study the biology of F. arisanus in C. capitata and A. fraterculus . Eggs of the two fruit fly species were used to determine the parasitism rate, number of offspring, emergence rate, sex ratio, adult weight and longevity of male and female F. arisanus . These biological parameters were used to develop a fertility life table. We observed higher parasitism and emergence rates of adults, a shorter duration of the egg–adult period and a sex ratio biased to females when F. arisanus was reared in eggs of C. capitata than in those of A. fraterculus . However, adults of F. arisanus from eggs of A. fraterculus were heavier and had greater longevity than those obtained from C. capitata eggs. The fertility life table showed better biological and reproductive performance for F. arisanus reared in eggs of C. capitata, although eggs of A. fraterculus also provided positive values for population increase.